Two genera of Panchaetothripinae newly recorded from China, with first description of males of Opimothrips tubulatus (Thysanoptera, Thripidae) - Xie, Yanlan; Li, Yajin; Li, Zhengyue; Zhang, Hongrui (Zootaxa, 2019)
The subfamily Panchaetothripinae comprises 40 extant genera worldwide (ThripsWiki 2019), although only 15 genera are previously recorded from China (Mirab-balou et al. 2016; Li et al. 2018). Panchaetothripinae thrips are characterized by the strong reticulations on the body and leg. Wilson (1975) recognized three tribes in this subfamily, Panchaetothripini, Monilothripini and Tryphactothripini, but only tribe Tryphactothripini was relatively supported based on morphological characters (Mound et al. 2001). Species in this Tribe have abdominal segment II constricted at the base and bearing laterally patches of strong ridges, wart-like tubercles or stoutly recurved microtrichia, and abdominal segment X tends to be asymmetrical. Recently, two further genera of Tryphactothripini were found in Southern China, Noathrips and Opimothrips. These two monotypic genera are reported only from the Old World tropics, Noathrips from India and Sri Lanka, and Opimothrips only from Thailand (Bhatti 1967; Kudô 1979; Nonaka & Okajima 1992). The purpose of this paper is to record these two genera from China, together with the first description of the male of Opimothrips tubulatus.